Crustose Coralline Algae and a Cnidarian Neuropeptide Trigger Larval Settlement in Two Coral Reef Sponges - Whalan, Steve (Public Library of Science, 2012)
In sessile marine invertebrates, larval settlement is fundamental to population maintenance and persistence. Cues contributing to the settlement choices and metamorphosis of larvae have important implications for the success of individuals and populations, but cues mediating larval settlement for many marine invertebrates are largely unknown. This study assessed larval settlement in two common Great Barrier Reef sponges, Coscinoderma matthewsi and Rhopaloeides odorabile, to cues that enhance settlement and metamorphosis in various species of scleractinian coral larvae. Methanol extracts of the crustose coralline algae (CCA), Porolithon onkodes, corresponding to a range of concentrations, were used to determine the settlement responses of sponge larvae. Cnidarian neuropeptides (GLW-amide neuropeptides) were also tested as a settlement cue. Settlement in both sponge species was approximately two-fold higher in response to live chips of CCA and optimum concentrations of CCA extract compared to 0.2 µm filtered sea water controls. Metamorphosis also increased when larvae were exposed to GLW-amide neuropeptides; R. odorabile mean metamorphosis reached 42.0±5.8% compared to 16.0±2.4% in seawater controls and in C. matthewsi mean metamorphosis reached 68.3±5.4% compared to 36.7±3.3% in seawater controls. These results demonstrate the contributing role chemosensory communication plays in the ability of sponge larvae to identify suitable habitat for successful recruitment. It also raises the possibility that larvae from distinct phyla may share signal transduction pathways involved in metamorphosis.